The Memory of the Stone - Daflon, Claudete (2011)
Based on the discussion proposed by Susan Sontag, Philippe Dubois and Edmond Couchot, it is possible to rethink photography as a way to disrupt the alleged continuity of time, as it petrifies any given instant suddenly made the witness to a lost moment. Brassaï focuses on the relationship with memory in Marcel Proust sous l’emprise de la photographie, relying on the photographic notion of “development” as a process in which memory comes into being only upon its evocation, as actualization of virtual existence. Accordingly, we propose an approach to Drummond’s poetry as photograph, especially when it focuses on ‘family portrait’. Considered the importance of origin marks in Drummond’s work, we seek to discuss them as both matrices of reading and “development” of the writing/photograph of the family, birthplace and childhood. Itabira is thus reconfigured as a space-time instance, the poet`s stone-like burden, in tension with the relativization of the patriarchal family provided by photographic ambiguity.